2017
DOI: 10.18632/oncotarget.22806
|View full text |Cite
|
Sign up to set email alerts
|

GATA3-induced vWF upregulation in the lung adenocarcinoma vasculature

Abstract: Lung adenocarcinoma (LAC) is the leading cause of cancer-related death worldwide. Aberrant expression of genes expressed preferentially in the lung tumor vasculature may yield clues for prognosis and treatment. Von Willebrand factor (vWF) is a large multifunctional glycoprotein with a well-known function in hemostasis. However, vWF has been reported to exert an anti-tumor effect, independent of its role in hemostasis. We investigated the expression of vWF in LAC through immunohistochemical staining of tumor ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…We observed a significant increase in the number of blood vessels (αSMA + cells) in HF mice compared to LF mice, and this number was further increased in HF‐LF cycled mice (Figure E). Moreover, HF‐LF cycled mice exhibited increased mRNA levels of angiogenic factors such as Vegfa (vascular endothelial growth factor A) and Vwf (von Willebrand factor), but not Vegfb , compared to those of HF and LF mice (Figure F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a significant increase in the number of blood vessels (αSMA + cells) in HF mice compared to LF mice, and this number was further increased in HF‐LF cycled mice (Figure E). Moreover, HF‐LF cycled mice exhibited increased mRNA levels of angiogenic factors such as Vegfa (vascular endothelial growth factor A) and Vwf (von Willebrand factor), but not Vegfb , compared to those of HF and LF mice (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…n = 3-6 per group. *P < .05 compared with LF group; # P < .05 compared with HF group factors such as Vegfa (vascular endothelial growth factor A 33 ) and Vwf (von Willebrand factor 34 ), but not Vegfb, compared to those of HF and LF mice ( Figure 3F).…”
Section: F I G U R Ementioning
confidence: 97%
“…Accumulating evidence has shown that GATA3 play key roles in cancer development. 28 30 Here, we first revealed that GATA3 was downregulated in OS. CCK-8 assay and colony formation assay demonstrated that GATA3 inhibited OS cells proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…Together, our results suggested that plasma level of vWF is an indicator for the risk of MACEs among patients with CAD. vWF is mainly synthesized in endothelial cells [25,26]. Upon endothelial cell injury, vWF is released into the blood circulation.…”
Section: Discussionmentioning
confidence: 99%